Age estimation by chest plate radiographs in a Thai male population - Monum T. (2017)
© 2017 Costal cartilage ossification on chest plate radiographs is one of the useful methods in age estimation for adults. This study was performed in 136 remains yielding a regression formula for age estimation in Thai male population. Eight features on chest plate imaging were scored based on Garvin's method. Composite scores were calculated by summation of all scores and analyzed to generate the regression of age as: Age = 16.664 × e 0.161 (composite score) with a 95% prediction interval. The predicted age intervals in all composite scores were overlapping except for score 0 and 7. It could be concluded that if all features are absent/present, the person is likely to be less/more than 29 years old.